A Co(II) compound: photocatalytic activity and application value in trigeminal neuralgia with minimally invasive interventional therapy guided by CT. Issue 1 (31st December 2022) - Wang, Shu-Wen; Li, Ling-Chao
ABSTRACT: A new thermostable Co(II)-based compound, namely [Co3 (L)2 (HTEA)2 ]n (1, HL = isonicotinic acid, H3 TEA = triethanolamine), has been successfully synthesized by the isomicotinic acid ligand and HTEA anion. The photocatalytic property of 1 was also investigated, indicating that it shows excellent photocatalytic activity for the degradation of Rhodamine B (MB) solution under the UV light irradiation. For the treatment of trigeminal neuralgia, the content of the inflammatory cytokines released into the trigeminal ganglion tissue fluid was measured with enzyme-linked immunosorbent assay (ELISA) assay. Then, the real-time Reverse Transcription-Polymerase Chain Reaction (RT-PCR) was conducted and the activation of the nuclear factor kappa-B (NF-κB) inflammatory signaling pathway was measured.